Turner syndrome and spontaneous pregnancy - Alessandra Bernadete Trovó de Marqui (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT The objective of this study is to describe patients with Turner syndrome (TS) who had spontaneous pregnancy and, when possible, to present the frequency of this outcome in this genetic condition. This is a literature review conducted in MedLine/PubMed, using the following English descriptors: Turner syndrome and spontaneous pregnancy. The following filters have been activated: articles with a publication date from the last 10 years that present the descriptors in the title/abstract. Twenty-nine articles were identified using the electronic search. After applying the inclusion and exclusion criteria, the number of articles selected was seven. However, two more articles were included after consulting the reference lists of these seven studies, totaling nine scientific articles. The frequency of spontaneous pregnancy ranged from 1.26% to 5.6%. Sixty-two TS patients who spontaneously became pregnant and 153 pregnancies were reported. There was a predominance of karyotype 45,X/46,XX (42 patients). Three patients were diagnosed with TS in adulthood and two of them after pregnancy. The minimum age at pregnancy was 21 years and the maximum 32. In the gestational outcome, an expressive number of children born, and abortions were observed, the latter with values of 54.9% and 34.6%. The present study described patients with TS and spontaneous pregnancy with mosaic (more frequent) and pure karyotype. It is believed that this value may be underestimated, since few studies have investigated primarily spontaneous pregnancy in this genetic condition, and many TS patients may not have been diagnosed because of the wide phenotypic variability associated with this chromosomal abnormality.